Research on Greenhouse Gas Inventory at DM Beer and Beverage Joint Stock Company, Quang Ninh Province - Van Doanh, Vu; Ngoc Thuan, Le; Thi Linh Giang, Nguyen; Thi Huyen, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2025)
According to the 2020 greenhouse gas (GHG) inventory data calculated by the Institute of Agricultural Environment, Vietnam's total GHG emissions reached about 454.6 million tons of CO₂e, nearly double that of 2010. Vietnam currently ranks seventeenth in the world in GHG emissions. Many businesses, especially small and medium-sized enterprises, have difficulty in GHG inventory due to lack of technical, financial, and awareness resources. The Decree 06/2022/ND-CP, Law on Environmental Protection 2020 and Decision 13/2024/QD-TTg clearly stipulate the requirements for GHG inventory for establishments under the government management list. DM Beer and Beverage Joint Stock Company is in this list with an energy consumption of 3,098 TOE. The results of the 2024 GHG emission inventory of DM Beer and Beverage Joint Stock Company show that the total converted emissions are 4,247,289.59 kg CO₂e, equivalent to 4,247.29 tons CO₂e. Researching the GHG inventory from the manufacture can inform if the company complies with the government legal requirements, evaluate its environmental management efficiency, and move towards sustainable development.